SPATIAL DISTRIBUTION OF SILICON AVAILABILITY IN THE HIGHLAND PADDY FIELDS OF WEST SUMATERA, INDONESIA - Adilla Sy Mahdiyah; Hermansah; Gusnidar; Maulana Insanul Kamil (BPFP Universitas Bengkulu, 2024)
Silica (Si) is a functional element in rice fields that is rarely studied, especially in Solok Regency. Intensive management without a fallow period causes silica to be transported out through high uptake by rice plants. This research aims to determine the distribution of available Si in the highland rice fields in Gunung Talang District, Solok Regency, West Sumatra. The research was carried out using a survey method. Soil samples were taken following the topo-sequence of the area of 600–1,100 meters above the sea level, which consists of 3 groups of rice fields based on height differences, namely the lower, middle, and upper fields. These rice fields have two types of straw management, namely burning and immersing. The research showed that the available Si content was 10.48–293.66 mg/kg with an average of 133.34 mg/kg. The available Si content is higher in the upper paddy fields compared to the lower and middle paddy fields. Based on differences in straw management, the available Si content is lower in fields with straw buried compared to burned straw. The application of Si fertilizer is highly recommended to obtain the available Si content in the soil.